Social Welfare Programs in India: Effectiveness and Economic Impact - Chaudhary, Garima (Integrated Journal for Research in Arts and Humanities, 2024)
Social welfare programs in India have been central to addressing the socio-economic disparities and poverty in the country. These programs have evolved over the years to cater to the needs of the marginalized sections of society, including the poor, elderly, women, children, and rural populations. This paper examines the effectiveness and economic impact of social welfare programs in India. We review major programs such as the Public Distribution System (PDS), National Rural Employment Guarantee Act (NREGA), Pradhan Mantri Jan Dhan Yojana (PMJDY), and others, assessing their outcomes on poverty alleviation, economic growth, and social inclusion. Additionally, we explore the challenges faced in their implementation and propose potential reforms to enhance their effectiveness.